OPTIMALISASI MANAJEMEN HUBUNGAN MASYARAKAT DALAM MENINGKATKAN KETERLIBATAN WALI MURID DI SDN TREWUNG - Diauddin; Wahidmurni; Fahim Tharaba; M Mahbubi (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This study aims to explore the role of public relations (PR) management in enhancing the relationship between schools and parents at SDN Trewung, Grati District, Pasuruan Regency. By employing a qualitative approach with a case study design, the research investigates the strategies implemented by the school to improve communication and increase parental involvement in the educational process. The findings reveal that open communication, regular meetings, social media utilization, and collaborative activities play crucial roles in strengthening the relationship between the school and parents. Regular meetings provide a platform for parents to express their views, share feedback, and engage with the school, fostering a stronger sense of partnership. Social media, as a tool for quick and efficient communication, facilitates information dissemination, overcoming geographical and time barriers. Collaborative activities, such as workshops and training for parents, further empower them to support their children's learning at home. The research also highlights the challenges, particularly the digital divide, which affects some parents' access to online communication platforms. Overall, the study emphasizes that effective PR strategies contribute significantly to enhancing parental involvement, thus supporting the success of students’ education. The findings offer valuable insights for other schools, particularly in rural areas, in developing effective PR strategies to engage parents in the educational process.